VD_FINDINFO HC / 2019 / 965 vom 30. Oktober 2019 - VD Tribunal cantonal (2019)
RÉVISIONDÉCISION, TRANSACTION JUDICIAIRE, CRAINTE FONDÉE, EXÉCUTION FORCÉE | 29 CO, 328 CPC (CH), 332 CPC (CH), 341 CPC (CH)